Chromosome-Level Genome Assembly of the Butter Clam Saxidomus purpuratus. (26th July 2022) - Kim, Jungeun; Kim, Hui-Su; Choi, Jae-Pil; Kim, Min Sun; Woo, Seonock; Kim, Yeonghye; Jo, Yejin; Yum, Seungshic; Bhak, Jong
Abstract: Herein, we provide the first whole-genome sequence of the purple butter clam ( Saxidomus purpuratus ), an economically important bivalve shellfish. Specifically, we sequenced and de novo assembled the genome of Sa. purpuratus based on PromethION long reads and Hi-C data. The 978-Mb genome of Sa. purpuratus comprises 19 chromosomes with 36, 591 predicted protein-coding genes. The N50 length of Sa. purpuratus genome is 52 Mb, showing the highest continuous assembly among bivalve genomes. The Benchmarking by Universal Single-Copy Orthologs assessment indicated that 95.07% of complete metazoan universal single-copy orthologs ( n = 954) were present in the assembly. Approximately 51% of Sa. purpuratus genome comprises repetitive sequences. Based on the high-quality Sa. purpuratus genome, we resolved half of the immune-associated genes, namely, scavenger receptor (SR) proteins, which are collinear to those in the closely related Cyclina sinensis genome. This finding suggested a high degree of conservation among immune-associated genes. Twenty-two (19%) SR proteins are tandemly duplicated in Sa. purpuratus genome, suggesting putative convergence evolution. Overall, Sa. purpuratus genome provides a new resource for the discovery of economically important traits and immune-response genes.